Evaluación de la calidad de las Especificaciones Técnicas en Obra Civil en base a la Relación Expectativa-Realidad - Román Salazar, Dayanna Carolina (2019)
The technical specifications document is made up of all the items that the construction project has, each item must have 7 basic sections that provide adequate and accurate information for decision making that requires its correct execution. However, little is known about the quality that they present, since has been identified that there are problems in the design of the projects and therefore in the elaboration of the technical specifications that are delivered and accepted with several design errors, thus leading to the breach of them. The objective of this research was to evaluate the quality of the technical specifications in civil works based on the expectation-reality relationship, for this purpose an on-site evaluation was carried out on working days and hours to a total of 176 items that were being executed or They have been executed recently, in 30 projects located in Zone 3 of Ecuador. Using the SPSS software for the processing and interpretation of the data obtained in graphs and summary tables. The results of the investigation show a 39.81% quality of the technical specifications for the analyzed sample, which justifies the problems mentioned in other investigations, of course, is the example of the increase in cost and term that has been evidenced in many contracts.